2022
DOI: 10.26641/2307-0404.2022.1.254369
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of CYP3A4*1G gene as a predictor of the hepatotoxicity of antituberculosis therapy

Abstract: The risk of anti-tuberculosis (ATB) drug-induced liver injury could be determined by genotype polymorphism of the xenobiotic-metabolizing enzymes. The aim of presented research was the investigation of an impact of CYP3A4*1G polymorphism on liver function in patients with TB during anti-tuberculosis therapy. There were analyzed case histories of 105 patients with newly diagnosed pulmonary TB at Odessa Regional TB Hospital in 2012-2014. We have considered their medical records at the beginning and at the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The presence of rs2242480 and rs2740574 polymorphisms might play a key role in increasing the risk of death in methadone use [11]. Previously it was found that in slow metabolizers according to CYP3A4*1G genotype after completion of in-patient stage of anti-TB treatment the level of cytolysis and toxicity indexes was much higher than in rapid metabolizers [12]. The aim of the present research was to find the meaning of CYP3A4*1В polymorphism in TB patients for the level of isoniazid and rifampicin as well as for the outcome and toxicity development during in-patient TB treatment.…”
Section: клінічна практикаmentioning
confidence: 99%
“…The presence of rs2242480 and rs2740574 polymorphisms might play a key role in increasing the risk of death in methadone use [11]. Previously it was found that in slow metabolizers according to CYP3A4*1G genotype after completion of in-patient stage of anti-TB treatment the level of cytolysis and toxicity indexes was much higher than in rapid metabolizers [12]. The aim of the present research was to find the meaning of CYP3A4*1В polymorphism in TB patients for the level of isoniazid and rifampicin as well as for the outcome and toxicity development during in-patient TB treatment.…”
Section: клінічна практикаmentioning
confidence: 99%